Analysis of Factors Affecting the Competitiveness of Salt in Tuban District - Rachmad Dian Kuncoro; Soemarno Soemarno; Andi Kurniawan (Faculty of Fisheries and Marine Science, Brawijaya University, 2022)
One of the important commodities for the Indonesian people produced from the marine sector is salt. The variety of salting problems has more or less affected the competitiveness of people's salt in each region in Indonesia. This condition clearly affects the welfare of salt farmers, because the selling price of salt received by farmers tends to be low. Tuban Regency is a coastal area that contributes to the achievement of salt production targets in East Java. Geographically, Tuban Regency is in the middle of salt processing areas, namely Surabaya-Gresik and Pati-Rembang, where these areas are also salt producing areas as well. Seeing this phenomenon, this study was conducted to analyze what factors affect the competitiveness of local salt in Tuban Regency. This study used primary data with a total of 90 respondents conducted randomly or random sampling. The analysis tool used is factor analysis. The research location was carried out in the salt production center area in Tuban regency, namely in Palang district and Tambakboyo district. From the results of the analysis, the results were obtained that there were five (5) factors that affect the competitiveness of local salt in Tuban Regency from the most influential to the factors that had the least influence, namely (1) Government Assistance, (2) Supporters, (3) Production Time and Government Regulations, (4) Social, and (5) Production and Post-Production.